2015
DOI: 10.1021/acs.energyfuels.5b02277
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Brine Salinity on the Stability of Hydrate-in-Oil Dispersions and Water-in-Oil Emulsions

Abstract: The stability of hydrate-in-oil dispersions is a critical parameter in assessing the risk of flowline blockage due to particle aggregation or wall deposition. Many studies of hydrate particle transportability have used deionized water to form the dispersion; however, the resulting lack of ions means that the crude oil's natural surfactants will be less active, which does not represent production conditions. This study presents a new investigation of both hydrate-in-oil dispersion stability and water-in-oil emu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
22
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 30 publications
(24 citation statements)
references
References 50 publications
2
22
0
Order By: Relevance
“…Figure 4.17b shows that similar results with CaCl2. Aman et al (2015) observed a similar reduction in droplet size (by up to 50%) after 24 hours of settling when the salt content increased from 0 to 4 wt% NaCl in model water-in-crude oil emulsions.…”
Section: Apparent Molecular Weight Of Interfacial Materialsmentioning
confidence: 53%
See 2 more Smart Citations
“…Figure 4.17b shows that similar results with CaCl2. Aman et al (2015) observed a similar reduction in droplet size (by up to 50%) after 24 hours of settling when the salt content increased from 0 to 4 wt% NaCl in model water-in-crude oil emulsions.…”
Section: Apparent Molecular Weight Of Interfacial Materialsmentioning
confidence: 53%
“…It has been documented by some authors that salts can reduce the drop size and created more stable emulsions (Aman et al, 2015;Marquez et al, 2010). However, other authors have reported the opposite effect, higher droplets and less stable emulsions, with an increase in salt content (Moradi et al, 2013).…”
Section: Table 23 Chemical Compositionmentioning
confidence: 99%
See 1 more Smart Citation
“…Water-in-oil emulsions were created with deionized water and an industrial crude oil previously described by Aman et al [27,28] with a respective density and viscosity of 0.85 g/ml and 4.7 cP at 20 °C and atmosphere pressure. Asphaltenes are contained in this crude oil, which contributes to the stabilization of the water-in-oil emulsion.…”
Section: Emulsion Preparation and Characterizationmentioning
confidence: 99%
“…The aims of the work presented here are to apply these PFG NMR techniques to monitor the effect of three different industrially available hydrate AAs on W/O emulsion stability (assessed via monitoring the temporal evolution in droplet size distributions) as a complement to traditional bottle stability tests. Turner et al (2009) and (Aman et al 2014(Aman et al , 2015 1 3…”
Section: Introductionmentioning
confidence: 99%